Pengaruh Pembiayaan Ijarah, Non-Performing Financing Dan Financing To Deposit Ratio Terhadap Return On Assets Pada Unit Usaha Syariah Tahun 2018-2020 - Rini Malinda Sari; Fena Ulfa Aulia; Iis Nurul Anami; Atika Salsabila (JPS (Jurnal Perbankan Syariah), 2021)
This study aims to determine the effect of ijarah financing, non-performing financing (NPF) and financing to deposit ratio (FDR) on return on assets (ROA) in Islamic business units (IBU) in 2018-2020. In this study, secondary data is used in the form of published quarterly financial reports of Islamic business units which are obtained from the website of the Financial Services Authority. The method used in this research is multiple linear regressions. The results of this study indicate that partially the ijarah financing variable has no significant effect on ROA, while NPF and FDR affect ROA. Ijarah financing cannot be used as a partial determining factor for ROA for IBU, but simultaneously ijarah financing, NPF and FDR can be used as a determining factor for ROA for IBU. Stakeholders can use the NPF and FDR variables as determinants of the level of ROA of an IBU.